Pengembangan Pariwisata Kreatif Berbasis Kearifan Lokal dalam Perspektif Collaborative Governance Studi di Kampung Blangkon Potrojayan Kelurahan Serengan Kecamatan Serengan Kota Surakarta - Muhamad Abdel Apalso; Kristina Setyowati (Jurnal Administrasi Publik, 2022)
Creative tourism is a form of tourism concept that is responsible for the existence of local communities. The city of Surakarta, which is a city with a process of historical growth and development, has made the city of Surakarta city formed from local wisdom, in which case the Blangkon Potrojayan village in Serengan Village, Serengan District is a form of physical heritage that can still be found, but over time the Blangkon Potrojayan village has been degraded since the last 20 years. This study aims to determine the collaboration process between stakeholders and the obstacles that occur in the collaboration process so that it can become a recommendation for the government, private sector and the community to optimize collaboration. The theory used in this study is the collaborative process theory of Anshel and Gash where there are five stages of collaboration, namely (1) face-to-face dialogue, (2) building trust (3) commitment to the process (4) mutual understanding, and (5) intermediary outcomes, while the method used in this research is descriptive qualitative. The results of this study indicate that the process of collaborative governance in the development of creative tourism based on local wisdom, in the process this collaboration has been going well, but there are still various obstacles such as the absence of communication forums, sectoral ego by each Stakeholder, limited resources, and less optimal role of the actors involved.